WE ALL LOVE A GOOD MEDICAL DRAMA – BUT ARE THEIR DEPICTIONS OF CPR BAD FOR THE PUBLIC?. Issue 12 (18th November 2016) - Welman, T; Welman, T; Williams, C; Bryan, J; Colwill, M; Lindberg, E; Somerville, C
Abstract : Objectives & Background: Out of hospital cardiac arrests (OHCS) are frequent worldwide but have disappointingly poor outcomes. Non medically trained individuals have been identified to perform substandard CPR by exerting less force than required to achieve adequate cardiac output. We have noticed that televised medical dramas often portray poor quality CPR. We set out to identify how well televised medical dramas depict cardiopulmonary resuscitation (CPR) and whether public knowledge of CPR technique is influenced by these programmes. Methods: We performed a prospective observational study of three popular medical dramas: Grey's Anatomy, Casualty and Holby City. A short survey was distributed amongst non-medically trained personnel to investigate public knowledge of CPR technique. Rate and depth of chest compressions depicted on screen and selected as correct by survey participants were evaluated. Results: 90 episodes were reviewed over the study period with 39 resuscitation attempts shown. Rate of chest compressions varied from 60 to 204 compressions per minute with a median of 122 (95% confidence interval 113 to 132). Depth varied from one to six centimetres with a median of two (2.1 to 2.87). Both the rate and depth observed were found to be significantly different from the UK Resuscitation Council Guidelines (2010) (p<0.05, t-test). Survey participants (n=160, response rate of 80%) documented what they thought was the correct rate and depth of chest compressions and were scored accordingly. Those who documented watching medical dramas regularly, scored significantly worse than those who only tune in occasionally (p<0.05, Mann Whitney test). Conclusion: Televised medical dramas often depict an inaccurate portrayal of CPR and members of the public are significantly less well-informed about the technique the more they tune into these popular programmes. The authors recommend that television producers improve the depiction of CPR on television to mimic the national guidelines.